Shock Wave Treatment Protects From Neuronal Degeneration via a Toll‐Like Receptor 3 Dependent Mechanism: Implications of a First‐Ever Causal Treatment for Ischemic Spinal Cord Injury. Issue 10 (27th October 2015) - Lobenwein, Daniela; Tepeköylü, Can; Kozaryn, Radoslaw; Pechriggl, Elisabeth J.; Bitsche, Mario; Graber, Michael; Fritsch, Helga; Semsroth, Severin; Stefanova, Nadia; Paulus, Patrick; Czerny, Martin; Grimm, Michael; et al.
Abstract : Background: Paraplegia following spinal cord ischemia represents a devastating complication of both aortic surgery and endovascular aortic repair. Shock wave treatment was shown to induce angiogenesis and regeneration in ischemic tissue by modulation of early inflammatory response via Toll‐like receptor (TLR) 3 signaling. In preclinical and clinical studies, shock wave treatment had a favorable effect on ischemic myocardium. We hypothesized that shock wave treatment also may have a beneficial effect on spinal cord ischemia. Methods and Results: A spinal cord ischemia model in mice and spinal slice cultures ex vivo were performed. Treatment groups received immediate shock wave therapy, which resulted in decreased neuronal degeneration and improved motor function. In spinal slice cultures, the activation of TLR3 could be observed. Shock wave effects were abolished in spinal slice cultures from TLR3 −/− mice, whereas the effect was still present in TLR4 −/− mice. TLR4 protein was found to be downregulated parallel to TLR3 signaling. Shock wave–treated animals showed significantly better functional outcome and survival. The protective effect on neurons could be reproduced in human spinal slices. Conclusions: Shock wave treatment protects from neuronal degeneration via TLR3 signaling and subsequent TLR4 downregulation. Consequently, it represents a promising treatment option for the devastating complication of spinal cord ischemia after aortic repair.